2001
DOI: 10.1076/stra.9.1.13.711
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmodynamometry: a reliable method for measuring intracranial pressure

Abstract: Under physiological conditions, the pressure in the central retinal vein is equal to or higher than the intracranial pressure (ICP) because the cerebrospinal fluid (CSF) passes the sheath of the optic nerve before draining into the cavernous sinus. The optic nerve sheath is where the ICP affects the retinal venous pressure. Ophthalmodynamometry (ODM) is a useful method for determining the central retinal artery pressure. While papilledema and a lack of venous pulsations are commonly used as a vague indication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 2 publications
2
26
0
1
Order By: Relevance
“…The pressure from the ophthalmodynamometer is converted to mmHg and added to the baseline IOP, giving the venous outflow pressure of the central retinal vein [59]. There is a close linear relationship between venous outflow pressure and ICP [60][61][62]. Further studies are needed to determine the sensitivity and specificity of this modality.…”
Section: Ophthalmodynamometrymentioning
confidence: 98%
“…The pressure from the ophthalmodynamometer is converted to mmHg and added to the baseline IOP, giving the venous outflow pressure of the central retinal vein [59]. There is a close linear relationship between venous outflow pressure and ICP [60][61][62]. Further studies are needed to determine the sensitivity and specificity of this modality.…”
Section: Ophthalmodynamometrymentioning
confidence: 98%
“…These techniques are invasive, and carry the risk of complications such as infections and damage to the neural structures. Since it is, therefore, desirable to have a non-invasive method to estimate the intracranial pressure, and based on a previous report about the use of a modified type of ophthalmodynamometry for assessment of the intracranial pressure [1,2], it was the purpose of the present report to describe a patient in whom non-invasive determination of the central retinal vein pressure allowed an estimation of an elevated cerebrospinal fluid pressure.…”
Section: Introductionmentioning
confidence: 98%
“…47 When CSF pressures are above 10 mm Hg, a strong linear relationship exists between CSF pressure and the minimum IOP required to induce retinal vein pulsation [venous pulsation pressure (VPP)]. The VPP has been used to gauge CSF pressure in subjects with elevated CSF pressure, 48,49 and it had been proposed that absent spontaneous venous pulsation may indicate an appropriately counterbalanced CSF pressure, and hence be a positive prognostic sign in glaucoma. 50 The use of VPP to measure low CSF pressure seems limited as studies in dogs found that as CSF pressure fell below 7 mm Hg the VPP remained constant at 15 mm Hg (Fig.…”
mentioning
confidence: 99%